Long-term outcomes after the paediatric Ross and Ross-Konno procedures. (13th June 2021) - Schlein, Johanna; Ebner, Barbara Elisabeth; Geiger, Ralf; Simon, Paul; Wollenek, Gregor; Moritz, Anton; Gamillscheg, Andreas; Base, Eva; Laufer, Günther; Zimpfer, Daniel
Abstract: : OBJECTIVES: The Ross procedure is an attractive option for the management of aortic valve disease in paediatric patients. We reviewed our experience with the paediatric Ross procedure to determine survival and freedom from reoperation in the third decade after surgery. METHODS: We reviewed the data of 124 paediatric patients [71% male, median age at time of surgery 11.1 years (interquartile range 6–14.8 years); 63.7% bicuspid aortic valve], who underwent the Ross procedure at 2 tertiary centres from April 1991 to April 2020. The Ross-Konno procedures were performed on 14 (11.3%) patients. Deaths were cross-checked with the national health insurance database, and survival status was available for 96.8% of the patients. The median follow-up time was 12.1 years (interquartile range 3–18 years). RESULTS: There were 3 early and 6 late deaths. All early deaths occurred in patients aged <1 year at the time of surgery. The 25-year survival was 90.3%. Actuarial freedom from reoperation (linearized rates in parentheses) was as follows: Autograft reoperation was 90.8% (0.48%/patient-year) and right ventricular outflow tract (RVOT) reoperation was 67% (2.07%/patient year) at 25 years. The univariable Cox-proportional hazard analysis revealed younger age at time of surgery ( P < 0.001), smaller implanted valve size ( P < 0.001) and the use of a xenograft rather than a homograft ( P < 0.001) as predictors of RVOT reoperation. At multivariable Cox-proportional hazard analysis, only age was an independent risk factor for RVOT reoperation ( P = 0.041). CONCLUSIONS: The Ross and the Ross-Konno procedures are associated with good outcomes in paediatric patients. Reoperation of the RVOT is frequent and associated with younger age.